NAVIGATING CHALLENGES IN ESSAY AND ARTICLE WRITING - Esanova , Nafosat Fakhriddiovna; Akabirova, Kamola Shokirovna (Educational Research in Universal Sciences, 2023)
Writing essays and articles is a skill that transcends academic boundaries, extending into professional and personal spheres. However, mastering this craft is not without its challenges. Whether you are a student working on assignments or a professional creating content, several obstacles may arise. In this article, we will explore some common challenges and strategies to overcome them.